2021
DOI: 10.21070/jees.v6i1.1085
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the English needs of law department students in English for specific purposes

Abstract: This present study aims at investigating the students’ target needs in learning ESP Speaking of Law department students. The adapted version of Aliakbari & Boghayeri’s (2014) and Alsamadani’s (2017) questionnaire was used as the main instrument of this study to understand the 45 students’ perception about their needs in learning ESP speaking course. A mixed-method research design was implemented in this present research. Students’ responses were analyzed statistically using SPSS 16.0 by calculating the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The research about ESP needs analysis of law students had been universally investigated by previous researchers. Rumalessin and Farah (2021) confirmed that law students expect the ESP learning process, which concerns their future professional job most. Research conducted by Samsudin and Sukarismanti (2020) claimed that most law students considered speaking, the most challenging skill, to be the primary focus of the learning process.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The research about ESP needs analysis of law students had been universally investigated by previous researchers. Rumalessin and Farah (2021) confirmed that law students expect the ESP learning process, which concerns their future professional job most. Research conducted by Samsudin and Sukarismanti (2020) claimed that most law students considered speaking, the most challenging skill, to be the primary focus of the learning process.…”
Section: Introductionmentioning
confidence: 63%
“…Thoroughly reading, those previous research only focused on investigating law students' needs in terms of learning materials. This issue can be proven by previous research that analyzed the correlation between gaining work experience and the level of importance attached to areas of Law studied (Rumalessin & Farah, 2021). The study integrated the concepts of English skills and the genuine academic concern of students' learning needs (Nurie, 2017), determining the expected materials and preparing relevant teaching materials to improve the ability to speak English (Samsudin & Sukarismanti, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, they hopefully believe that their viewpoints can contribute to educational institutions with resourceful reference in redesigning and renovating the ESP curricula, especially legal English curriculum to match theory to practice. Similarly, Rumalessin and Farah (2021) conducted a mix-methods study on legal English necessity of graduates. They emphasize the needs of student access authentic legal materials relating to law cases.…”
Section: Recent Graduates' Perspectives Towards Career Developmentmentioning
confidence: 99%
“…So, the importance on the right and famous qualifications help recent graduates manage and succeed in their roles at workplace (Velden et al, 2015;Su-Hei et al, 2017;Cheang & Yamashita, 2020). It is advisable for employees to have qualified, professional expertise in their working positions with both good academic degrees and soft skills, specially ESP such as legal English language competence (Oliver, 2011;Rumalessin & Farah, 2021). Shockingly, employers evaluate moderately those graduates who obtain an English certificate or passing corporate English proficiency tests.…”
Section: Evaluating Legal English Language Skills During Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation